GOVERNMENT LEVERS IN THE DIGITAL ECONOMY - Azamov Sulaimon Mamatisakovich; Shokirova Sarvinoz Oybekovna (Scholar Express Journals, 2022)
Large volumes of data are generated and consumed by digital devices. This information may be utilized to improve citizen services, increase sectoral efficiency, help in the development of evidence-based policies, and enable stakeholders to make better decisions in general. Access to data and the capacity to use, re-use, and share information in a rights-respecting environment has the potential to solve numerous social, economic, and environmental issues while also offering chances for innovation, whether in current industries or by creating new ones entirely. In this article, various arguments about government levers in the digital economy are presented.
Keywords: Digital Economy; Government Levers; Digitalization; Data Security